Chemical Perturbation of Oncogenic Protein Folding: from the Prediction of Locally Unstable Structures to the Design of Disruptors of Hsp90–Client Interactions. Issue 43 (8th July 2020) - Paladino, Antonella; Woodford, Mark R.; Backe, Sarah J.; Sager, Rebecca A.; Kancherla, Priyanka; Daneshvar, Michael A.; Chen, Victor Z.; Bourboulia, Dimitra; Ahanin, Elham F.; Prodromou, Chrisostomos; Bergamaschi, Greta; Strada, Alessandro; et al.
Abstract: Protein folding quality control in cells requires the activity of a class of proteins known as molecular chaperones. Heat shock protein‐90 (Hsp90), a multidomain ATP driven molecular machine, is a prime representative of this family of proteins. Interactions between Hsp90, its co‐chaperones, and client proteins have been shown to be important in facilitating the correct folding and activation of clients. Hsp90 levels and functions are elevated in tumor cells. Here, we computationally predict the regions on the native structures of clients c‐Abl, c‐Src, Cdk4, B‐Raf and Glucocorticoid Receptor, that have the highest probability of undergoing local unfolding, despite being ordered in their native structures. Such regions represent potential ideal interaction points with the Hsp90‐system. We synthesize mimics spanning these regions and confirm their interaction with partners of the Hsp90 complex (Hsp90, Cdc37 and Aha1) by Nuclear Magnetic Resonance (NMR). Designed mimics selectively disrupt the association of their respective clients with the Hsp90 machinery, leaving unrelated clients unperturbed and causing apoptosis in cancer cells. Overall, selective targeting of Hsp90 protein–protein interactions is achieved without causing indiscriminate degradation of all clients, setting the stage for the development of therapeutics based on specific chaperone:client perturbation. Abstract : Cutting contact : A novel, fully rational computational approach predicts the unfolding/unstable regions of proteins. Designed synthetic mimics of such regions block protein interactions with chaperones in cells, and induce apoptosis in cancer cells.